Composition of Harpacticoida (Crustacea: Copepoda) during land reclamation activity in seagrass area of Sungai Pulai, Malaysia - Kassim, Zaleha; Nordin, Amira Syahidah; Ismail, Ahmad (2018)
Sungai Pulai is one of the largest areas for riverine mangroves which associated with other important ecosystem, the seagrass bed and mud flat located in the Tebrau Straits of Johor. The nearby area is experienced rapid development activities including land reclamation. This study is carried out to investigate the composition of copepods particularly the Harpacticoida group in the seagrass bed continuously exposed to such land activities. Core samples were taken from three stations which consist of vegetation and non vegetation areas in the evening during lowest tide in October and November 2017. All samples were fixed with 10% buffered formalin added with Rose Bengal stain. Seven families of harpacticoids were identified, Porcellidiidae Sars., Diossaccidae Sars., Longipediidae Sars, Lang., Laophontidae T. Scott., Canuellidae Lang., Tisbidae Stebbing, Lang and Paramesochridae Lang. Porcellidiidae. Result revealed that there is a significant different for Porcellidiidae density (F=5.512, p=0.002) between all harpacticoid copepod family member in all station except with Diosaccidae in the vegetation area. Overall, 2-Way Anova by using Duncan test showed the density of harpacticoid copepods in vegetation area is highly significant compared to non-vegetation area (F=4.512, p=0.005). In vegetation area, Pearson’s Correlation analysis summarized that Cannuellidae has strong correlation with Total Organic Matter, TOM (R=0.864) if compared to other families. In first sampling, family Porcellidiidae showed high significant correlation towards mean grain size and sorting condition of sediment which is R=1.000, p=0.018 and R=-0.997,p=0.049 respectively. Longipedidae also gave significant correlation towards sorting condition which is R=-0.999, p=0.025. Nonetheless, Tisbidae family showed high significant correlation to mean grain size which R=0.998, p=0.041during the second sampling. Porcellidiidae which is known as obligate phytal species does not affected by the amount of TOM but with sediment characteristic along with Longipedidae and Tisbidae, which indicate their composition could be easily affected by the change of sediment in the area.